2018
DOI: 10.1186/s13567-018-0540-z
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the pathology and tissue distribution of Lagovirus europaeus GI.2/RHDV2 (rabbit haemorrhagic disease virus 2) in young and adult rabbits (Oryctolagus cuniculus)

Abstract: Lagovirus europaeus GI.2, also known as RHDV2 or RHDVb, is an emerging virus that causes rabbit haemorrhagic disease (RHD) in European rabbits (Oryctolagus cuniculus). In contrast to L. europaeus GI.1 (or RHDV/RHDVa) viruses that are only pathogenic for adults, GI.2 causes clinical disease in both adults and kittens. However, detailed descriptions of the pathology of this virus that may provide insight into its pathogenicity and emergence are lacking. Using an Australian GI.2 field strain isolated in 2015, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 55 publications
7
79
1
Order By: Relevance
“…Its highly pathogenic nature was previously confirmed in SPF kits under experimental conditions (mortality rate of 100%). To our knowledge, only 2 small scale trials have been published on highly virulent GI.2 strains (Capucci et al, 2017;Neimanis et al, 2018). So, this challenge study was also the opportunity to describe the clinical course and virulence of the infection, in kits and adult rabbits, after experimental inoculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its highly pathogenic nature was previously confirmed in SPF kits under experimental conditions (mortality rate of 100%). To our knowledge, only 2 small scale trials have been published on highly virulent GI.2 strains (Capucci et al, 2017;Neimanis et al, 2018). So, this challenge study was also the opportunity to describe the clinical course and virulence of the infection, in kits and adult rabbits, after experimental inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Several GI.2/RHDV2/b outbreaks in unvaccinated farmed rabbits were characterised by higher mortality rates (Capucci et al, 2017). Experimental studies of GI.2 strains isolated in 2014 and 2015 in Italy, as well as recombinant GI.1bP-GI.2 strain isolated in Australia in 2015, confirmed that these recent viruses resulted predominantly in an acute disease unlike the earliest emerging strains (2010-2011), which often induced subacute and chronic form of RHD (Capucci et al, 2017;Neimanis et al, 2018). Mortality rates of at least 80% were recorded, which approached usual mortality rate described for GI.1/RHDV, and demonstrated an increase in pathogenicity of GI.2/RHDV2/b viruses.…”
Section: Introductionmentioning
confidence: 88%
“…Laboratory studies using experimental infections with early isolates of RHDV2 indicated that mortality rates due to RHDV2 infection were lower than RHDV, with a longer infectious period (Dalton et al, 2018;Le Gall-Reculé et al, 2013). However, other studies using more recent RHDV2 isolates report very high levels of virulence in both adult and young rabbits (Capucci, Cavadini, Schiavitto, Lombardi, & Lavazza, 2017;Neimanis, Pettersson, Huang, Widén, & Strive, 2018). Unlike RHDV (Robinson, So, Müller, Cooke, & Capucci, 2002), RHDV2 causes fatal infections in juvenile rabbits <5 weeks of age (Neave et al, 2018) and can also infect rabbits recovered from previous RHDV infection or vaccination (Le Gall-Reculé et al, 2013;Neave et al, 2018;Peacock et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, we may have expected to find more viruses of livestock (site 1) and native vertebrate species (site 1 and 2), which are abundant in the sampling locations. Hence, vertebrate-associated viral mechanical transmission by fly species may be uncommon, and factors such as high prevalence and high virus load in carcasses or faeces - as seen for RHDV-like viruses - may therefore be necessary for mechanical transmission (Mahar, Hall, et al, 2018; Neimanis, Larsson Pettersson, Huang, Gavier-Widen, & Strive, 2018). In contrast to flies, no vertebrate virus reads - including MYXV - were detected in fleas, although their behaviour of feeding on vertebrate blood rather than carcasses and faeces may limit opportunities for mechanical transmission to periods of acute systemic or viraemic infections.…”
Section: Discussionmentioning
confidence: 99%